Blended and online learning: a comparative study of virtual microscopy in Higher Education. Issue 6 (17th August 2020) - Herodotou, Christothea; Muirhead, Dave K.; Aristeidou, Maria; Hole, Malcolm J.; Kelley, Simon; Scanlon, Eileen; Duffy, Marcus
ABSTRACT: Virtual Learning Environments (VLEs) are becoming commonplace in Higher Education. Amongst the latest VLE developments is the design and use of Virtual Microscopes (VMs) that allow for viewing and manipulation of online images by multiple students. Although students are found to be generally satisfied with the use of VMs, it is yet not known what teaching and learning conditions better support their use and lead to enhanced learning outcomes. The aim of this paper is to compare the usage patterns and perceptions of two different cohorts of undergraduate students that made use of the VM in blended and online only learning conditions respectively, and draw conclusions about the pedagogy that better supports teaching and learning with VMs. Data collected from a survey with 139 students and 11 semi-structured interviews revealed that blended learning better caters for students' engagement and satisfaction due to the systematic use of the VM in course design, its complementary use with a physical microscope, and the ongoing provision of tutors' support and guidance. Equally good perceived learning gains were reported by both blended and online only students. Implications for the design of learning environments around virtual microscopy are discussed.